Answer:
x =
![(1)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/r8zl28n0vf0ogg71i3r53apxva24c1inf4.png)
y =
![(3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e14yosw5rbprbu04e78upb04bghif5atho.png)
z = 0
Explanation:
You first need to solve for a variable, it won't be as easy as x = 3, you are looking to replace a variable with another equation.
For example, the second equation, 4y-z=3, I can either solve for y or z. It won't be a numerical value but it will get you a step closer.
4y-z=3
4y=z+3
y =
![(z)/(4) +(3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/yct7wp5zat0hs8wdmyuklfhyauc8mcj0nq.png)
Then you are able to use substitution to negate one of the variables and solve for the other two variables. I won't type that but I think you get the idea.